2004
DOI: 10.1038/430630a
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected magnetism in a dielectric oxide

Abstract: It is generally accepted that magnetic order in an insulator requires the cation to have partially filled shells of d or f electrons. Here we show that thin films of hafnium dioxide (HfO2), an insulating oxide better known as a dielectric layer for nanoscale electronic devices, can be ferromagnetic even without doping. This discovery challenges our understanding of magnetism in insulators, because neither Hf4+ nor O2- are magnetic ions and the d and f shells of the Hf4+ ion are either empty or full.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
725
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,172 publications
(763 citation statements)
references
References 2 publications
25
725
2
3
Order By: Relevance
“…For thiol capped thin films the magnetization curves are fairly different upon applying field parallel or perpendicular to the surface (hence confirming the huge anisotropy) and the magnetic moments are giant [14,15]. Similar features (giant magnetic moments and huge anisotropy) have been observed for DMS thin films [10,11,17] suggesting a possible common origin of both effects. In this work we experimentally show that capping ZnO NPs with a variety of organic molecules modifies its electronic structure arising ferromagnetic-like behaviour up to 300 K. Therefore, this method opens a new way to obtain the desired magnetic semiconductors without using any type of magnetic atoms and avoiding the superparamagnetic limit.…”
Section: /11mentioning
confidence: 57%
See 2 more Smart Citations
“…For thiol capped thin films the magnetization curves are fairly different upon applying field parallel or perpendicular to the surface (hence confirming the huge anisotropy) and the magnetic moments are giant [14,15]. Similar features (giant magnetic moments and huge anisotropy) have been observed for DMS thin films [10,11,17] suggesting a possible common origin of both effects. In this work we experimentally show that capping ZnO NPs with a variety of organic molecules modifies its electronic structure arising ferromagnetic-like behaviour up to 300 K. Therefore, this method opens a new way to obtain the desired magnetic semiconductors without using any type of magnetic atoms and avoiding the superparamagnetic limit.…”
Section: /11mentioning
confidence: 57%
“…Rubi et al [9] found similar results for Co and Mn doped ZnO powder samples. Moreover, Coey et al [10] demonstrated that doping ZnO thin films with 3d non magnetic ions (as Ti or V) also leads to RT ferromagnetic behaviour and for insulating HfO2 the effect appear even without doping [11]. Those results point on the alteration of the electronic structure of the semiconductor (induced by both, the presence of the magnetic impurity and the defects) as responsible of the origin of the observed magnetism.…”
Section: /11mentioning
confidence: 99%
See 1 more Smart Citation
“…Dilute ferromagnetism in oxide semiconductors generally has been reported with 3d dopants in ZnO particularly with Mn, Co, Ni, Fe, Cu, and V dopings. [1][2][3] Unexpected magnetization without transition metal has been reported in dielectric oxides such as HfO 2 , ZrO 2 , 4 and nonmagnetic oxides, e.g., ZnO, 5 hexaborides, 6 carbon-doped ZnO, 7 and in irradiated graphite. 8 The theory of Dietl et al 9 suggests that carrier-induced ferromagnetism in Mn-doped p-type material may be observed at higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, doping of ZnO thin films with non-magnetic ions from the 3d group (e.g. titanium or vanadium) can cause emergence of ferromagnetic properties [9]. All these results indicate on a critical role of electronic structure of a semiconductor (modified by the presence of magnetic ions) in appearance of ferromagnetic properties.…”
Section: Introductionmentioning
confidence: 93%